Computational analysis of subscapularis tears and pectoralis major transfers on muscular activity. (February 2022) - Péan, Fabien; Favre, Philippe; Goksel, Orcun
Abstract: Background: Pectoralis major is the most common muscle transfer procedure to restore joint function after subscapularis tears. Limited information is available on how the neuromuscular system adjusts to the new configuration, which could explain the mixed outcomes of the procedure. The purpose of this study is to assess how muscles activation patterns change after pectoralis major transfers and report their biomechanical implications. Methods: We compare how muscle activation change with subscapularis tears and after its treatment by pectoralis major transfers of the clavicular, sternal, or both these segments, during three activities of daily living and a computational musculoskeletal model of the shoulder. Findings: Our results indicate that subscapularis tears require a compensatory activation of the supraspinatus and is accompanied by a reduced co-contraction of the infraspinatus, both of which can be partially recovered after transfer. Furthermore, although the pectoralis major acts asynchronously to the subscapularis before the transfer, its activation pattern changes significantly after the transfer. Interpretation: The capability of a transferred muscle segment to activate similarly to the intact subscapularis is found to be dependent on the given motion. Differences in the activation patterns between intact subscapularis and the segments of pectoralis major may explain the difficulty in adapting psycho-motor patterns during the rehabilitation period. Thereby, rehabilitation programs could benefit from targeted training on specific motion and biofeedback programs. Finally, the condition of the anterior deltoid should be considered to improve joint function. Highlights: Subscapularis and pectoralis major are not in sync during activities of daily living. Such patterns change significantly after transfer depending on considered motion. Tested transfers restore activation of rotator cuff muscles toward intact baseline. Anterior deltoid strength is key in the transfer of pectoralis major clavicular part. Musculoskeletal simulation of active motion reveals new insights on muscle transfers.